2014
DOI: 10.1007/s10680-014-9326-9
|View full text |Cite
|
Sign up to set email alerts
|

How Migration Affects the Timing of Childbearing: The Transition to a First Birth Among Polish Women in Britain

Abstract: Views differ on how migration affects the timing of childbearing. Whereas migration has long been considered a break in the life course, hindering family formation, this disruption hypothesis has recently been challenged. New findings indicating that there is often an acceleration of childbearing shortly after migration have led to the formulation of the interrelation hypothesis. Examining the childbearing behaviour of Polish women, this study extends previous research by combining information from the countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
1
37
1
Order By: Relevance
“…that fertility is particularly high immediately after migration. This link has been demonstrated for immigrants in the USA, France, Sweden, Spain, the UK, and the Netherlands (Alders 2000; Andersson 2004; Andersson and Scott 2005; Carter 2000; Choi 2014; Devolder and Bueno 2011; Lindstrom and Giorguli-Saucedo 2007; Lübke 2014; Singley and Landale 1998; Toulemon 2004). Studies on Spain and Italy showed that period fertility and first birth risks were particularly high shortly after arrival among women who migrated for family reasons (Mussino and Strozza 2012; Vila and Martìn 2007).…”
Section: Theoretical Considerations and Previous Researchmentioning
confidence: 88%
See 3 more Smart Citations
“…that fertility is particularly high immediately after migration. This link has been demonstrated for immigrants in the USA, France, Sweden, Spain, the UK, and the Netherlands (Alders 2000; Andersson 2004; Andersson and Scott 2005; Carter 2000; Choi 2014; Devolder and Bueno 2011; Lindstrom and Giorguli-Saucedo 2007; Lübke 2014; Singley and Landale 1998; Toulemon 2004). Studies on Spain and Italy showed that period fertility and first birth risks were particularly high shortly after arrival among women who migrated for family reasons (Mussino and Strozza 2012; Vila and Martìn 2007).…”
Section: Theoretical Considerations and Previous Researchmentioning
confidence: 88%
“…It is particularly difficult to distinguish the interrelation of childbirth and migration from selection effects (e.g. Lübke 2014; Milewski 2007). As noted by Lübke (2014), data on the country of origin are needed to disentangle selectivity issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, intra-EU migration presents the unusual opportunity to study fertility change in the reverse direction, i.e. whether the process of convergence is also observed among migrants originating from very low fertility countries in Eastern or Southern Europe that move to a higher fertility country within Europe (Waller et al 2014;Lübke 2015 on Polish immigrants in the UK). This would allow for an assessment of whether and how changes in economic, social, cultural and policy environment result in different fertility norms and behaviour.…”
Section: A Demographic Perspective On Eu Migrationmentioning
confidence: 99%